Comparative study of biological activities of extracts from three Malaysian Beilschmiedia species - W. Salleh, Wan Mohd. Nuzul Hakimi (MARMARA UNIVERSITYMarmara University, 2016)
This study was carried out to investigate the bioactivities of extracts from three Beilschmiedia species, which are Beilschmiedia glabra, B. madang, and B. pulverulenta. The bioactivity studies were determined on their antioxidant, antimicrobial, antityrosinase, anti-inflammatory, and acetylcholinesterase activities. Evaluation of antioxidant activities were tested against DPPH and phenolic content (TPC) assays. The antimicrobial activity were investigated by micro dilution method for determination of MIC, MBC and MFC. Antityrosinase and anti-inflammatory inhibition activity was analysed using mushroom tyrosinase and lipoxygenase enzyme, respectively, while acetylcholinesterase activity against acetylcholinesterase (AChE) enzyme. The MeOH stem bark extract of B. madang shows the highest activity on DPPH (IC50 of 63.2 μg/mL) and TPC (163.4 mg GA/g) assay. All extracts showed from moderate to weak activity with MIC/MBC/MFC values in the ranged of 125-1000 µg/mL. The EtOAc leaves extract of B. glabra revealed the highest percentage inhibition on tyrosinase activity (I: 82.5%), while for anti-inflammatory activity showed by the MeOH leaves extract of B. pulverulenta (I: 66.6%). The MeOH stem bark extract of B. madang demonstrated the highest activity on acetylcholinestrase activity with percentage inhibition of 62.8%. The results demonstrated that the Beilschmiedia species possess significant activities on various biological studies.